How Do Trade and Financial Integration Affect the Relationship Between Growth and Volatility? - Prasad, Eswar (IMF Working Papers; Working Paper ;, 2005)
The influential work of Ramey and Ramey (1995) highlighted an empirical relationship that has now come to be regarded as conventional wisdom-that output volatility and growth are negatively correlated. We reexamine this relationship in the context of globalization-a term typically used to describe the phenomenon of growing international trade and financial integration that has intensified since the mid-1980s. Using a comprehensive new data set, we document that, while the basic negative association between growth and volatility has been preserved during the 1990s, both trade and financial integration significantly weaken this negative relationship. Specifically, we find that, in a regression of growth on volatility and other controls, the estimated coefficient on the interaction between volatility and trade integration is significantly positive. We find a similar, although less significant, result for the interaction of financial integration with volatility.